Next-Generation Sequencing Analysis of Gastric Cancer Identifies the Leukemia Inhibitory Factor Receptor as a Driving Factor in Gastric Cancer Progression and as a Predictor of Poor Prognosis - Di Giorgio, Cristina; Marchianò, Silvia; Marino, Elisabetta; Biagioli, Michele; Roselli, Rosalinda; Bordoni, Martina; Bellini, Rachele; Urbani, Ginevra; Zampella, Angela; Distrutti, Eleonora; Donini, Annibale; Graziosi, Luigina; et al. (Frontiers in Oncology, 2022)
Gastric cancer (GC) is the third cause of cancer-related-death worldwide. Nevertheless, because GC screening programs are not cost-effective, most patients receive diagnosis in the advanced stages, when surgical options are limited because the presence of diffuse disease. Peritoneal dissemination occurs in approximately one third of patients with GC and is a strong predictor of poor outcome. Despite the clinical relevance, biological and molecular mechanisms underlying the formation of peritoneal metastasis in GC remain poorly defined. To investigate this point, we conducted a high-throughput sequencing of transcriptome expression in paired samples of normal and neoplastic gastric mucosa in 31 GC patients with or without peritoneal carcinomatosis. The RNAseq analysis led to the discovery of a group of highly upregulated or downregulated genes that were differentially modulated in patients with peritoneal disease in comparison to GC patients without peritoneal involvement. Among these genes, the Leukemia inhibitory factor receptor (LIFR) and the one cut domain family member (ONECUT)2 were the only two genes that predicted survival at univariate statistical analysis. Because LIFR was the highest regulated gene, we have further assessed whether this receptor plays a mechanistic role in GC dissemination. For this purpose, we have first assessed the expression of LIF, a member of IL-6 cytokine family, and LIFR in GC cell lines. Our results demonstrate that exposure of MKN45 cells to LIF promotes a concentration-dependent proliferation and epithelial-mesenchymal transition (EMT) as shown by modulation of E-cadherin/vimentin gene expression along with JAK and STAT 3 phosphorylation and acquisition of a migratory phenotype. These features were reversed by in vitro treatment with a LIFR antagonist. Together, these data provide support to the notion that development of LIF/ LIFR inhibitors might have a role in the treatment of GC.